Zakat Empowerment in Mustahiq Economic Recovery During the Covid-19 Pandemic - Ichsan Hamidi; Liliana Liliana; Gustriani Gustriani; Dirta Pratama Atiyatna; Dwi Darma Puspita Sari (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This study determined to examines zakat empowerment in mustahiq economic recovery during the Covid-19 pandemic. This study uses quantitative approaches using primary and secondary data through interviews, observation, and documentation. Methodology used in this study is a quantitative approach with multiple regression model. Population are mustahiq zakat who become a member in zakat productive program. Findings of this study indicated that zakat productive and length of business has a significant effect and positive correlation on mustahiq income during the Covid-19 pandemic. On this point the empowerment of zakat to recovery the mustahiq economic during this pandemic can be developed with more innovation, so that more mustahiq zakat got a better living through this program. This research is expected to maximizing the role of zakat empowerment to improve mustahiq welfare and can be a reference in developing sustainable programs in zakat empowerment in Indonesia.